2010
DOI: 10.1159/000322387
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Urinoma in Females without Obstructive Uropathy

Abstract: Objective: Prenatal diagnosis of urinomas has long been established with underlying obstructive uropathy generally responsible for urinary extravasation. Because urinoma formation represents a pop-off mechanism in cases of posterior urethral valves, the number of affected males greatly exceeds the number of females. Fetal urinoma has rarely been reported without obstruction and in females it has only been described as a consequence of a complicated amniocentesis. Methods: Three cases of fetal urinoma in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Thus, it seems safe to speculate that the etiology of the obstruction does not dictate whether spontaneous resolution will occur. Additional case reports have described resolution shortly after birth 13 . However, regression of the urinoma should be approached with caution, as it may reflect oliguria secondary to severe renal dysplasia rather than improvement in urine drainage or the obstruction itself.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems safe to speculate that the etiology of the obstruction does not dictate whether spontaneous resolution will occur. Additional case reports have described resolution shortly after birth 13 . However, regression of the urinoma should be approached with caution, as it may reflect oliguria secondary to severe renal dysplasia rather than improvement in urine drainage or the obstruction itself.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, urinomas are often described as consequences of blunt trauma, urinary tract obstruction by uroliths, intra-abdominal malignancy, retroperitoneal fibrosis or post instrumentation (Titton et al 2003;Goldwasser et al 2018). This condition is also described in foetuses mostly because of the urine extravasation after the rupture of the kidney second to an underlying urinary tract obstruction or trauma (Gorincour et al 2006;Zaccara et al 2011;Yitta et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[10] The occurrence of fetal urinomas has also been reported following a traumatic amniocentesis. [4] Additionally, Zaccara et al [11] reported three cases of fetal urinomas in female fetuses without an identifiable obstructive uropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The postnatal function of kidneys with urinomas and PUV has been previously reported to be between 20% and 71%. [6][7][8][9][10][11][12][13][14][15][16] In 1990, Fernbach et al [1] described 5 cases with PUV, in which renal function was preserved in the presence of a urinoma. However, later studies have not identified any protective effect for urinomas in PUV patients.…”
Section: Discussionmentioning
confidence: 99%